2019 27th European Signal Processing Conference (EUSIPCO) 2019
DOI: 10.23919/eusipco.2019.8902588
|View full text |Cite
|
Sign up to set email alerts
|

FPGA Implementation of a TVWS Up- and Downconverter Using Non-Power-of-Two FFT Modulated Filter Banks

Abstract: This paper addresses an oversampled filter bank (OSFB) approach to up-and down-convert any or all of the 40 channels in the United Kingdom's TV white space (TVWS). We particularly consider the use of non-power-of-two fast Fourier transforms (FFTs), which provides a greater choice of design parameters over existing OSFB implementations. Using a fieldprogrammable gate array (FPGA) software defined radio (SDR) platform, we compare two different 40-point FFT-based implementations of the system-one fully parallelis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The algorithm is effective in reducing the power consumption of the GHz PTMP radio, providing up to 3% energy saving against a maximum reach policy. Together with efforts towards a low-power basestation implementation [9], [28], [29], this algorithm can permit a downsizing of the power supply systems (harvesters and batteries), thus reducing the cost of the base station, as demonstrated in simulation by reducing the harvesting capacity of the BS to 25%. Furthermore the algorithm can provide a better balance between the number of users assigned to each of the networks, and is therefore capable of enhancing the quality of service.…”
Section: Resultsmentioning
confidence: 99%
“…The algorithm is effective in reducing the power consumption of the GHz PTMP radio, providing up to 3% energy saving against a maximum reach policy. Together with efforts towards a low-power basestation implementation [9], [28], [29], this algorithm can permit a downsizing of the power supply systems (harvesters and batteries), thus reducing the cost of the base station, as demonstrated in simulation by reducing the harvesting capacity of the BS to 25%. Furthermore the algorithm can provide a better balance between the number of users assigned to each of the networks, and is therefore capable of enhancing the quality of service.…”
Section: Resultsmentioning
confidence: 99%
“…slower) and can increase design complexity. That being said, it has been shown that under certain conditions non-power-of-2 FFTs can result in a reduction in hardware resources and power consumption [29].…”
Section: B Sub-optimal Algorithmsmentioning
confidence: 99%